2002
DOI: 10.1095/biolreprod67.4.1099
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Antrum Formation, and Estradiol Production of Bovine Preantral Follicles Cultured in a Serum-Free Medium1

Abstract: The objective of this study was to identify factors that would allow the establishment of a serum-free culture system that could support follicular and oocyte growth, antrum formation, and estradiol-17beta (E(2)) production in preantral follicles of bovine ovaries. Large preantral follicles (145-170 micro m in diameter) were microsurgically dissected from ovaries, embedded in 0.15% type I collagen gels, and maintained in a serum-free medium for up to 13 days at 38.5 degrees C in 5% CO(2) in air. This culture e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
3
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 44 publications
3
60
3
5
Order By: Relevance
“…Due to the protracted nature of preantral follicle development in large mammals, culture systems should be developed to accelerate oocyte growth, without inducing inappropriate follicular differentiation. A recent study has reported that recombinant IGF-I increased bovine preantral follicle and oocyte diameter during serum-free culture (Itoh et al 2002). By contrast, in a long-term culture system, LR3 IGF-I promoted bovine preantral follicle growth and antrum formation, but oocyte diameter was not increased .…”
Section: Discussionmentioning
confidence: 91%
“…Due to the protracted nature of preantral follicle development in large mammals, culture systems should be developed to accelerate oocyte growth, without inducing inappropriate follicular differentiation. A recent study has reported that recombinant IGF-I increased bovine preantral follicle and oocyte diameter during serum-free culture (Itoh et al 2002). By contrast, in a long-term culture system, LR3 IGF-I promoted bovine preantral follicle growth and antrum formation, but oocyte diameter was not increased .…”
Section: Discussionmentioning
confidence: 91%
“…FSH is known to stimulate follicular growth and maintain the integrity of granulosa cells in sheep (CECCONI et al, 1999) and cattle (SAHA, et al, 2000). FSH treatment was shown to stimulate oocyte growth in bovine pre-antral follicles in-vitro (ITOH et al, 2002). Culture of ovarian tissue in medium containing FSH resulted in in-vitro growth of caprine pre-antral follicles, while their ultrastructural integrity was maintained (ROSSETTO et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As there are FSH receptors in the granulosa cells of early follicles, it is possible that FSH may promote follicular growth and development (Méduri et al, 2002). Previous observations have showed that FSH promotes an increase in both oocyte (Itoh et al, 2002) and follicular diameter (Wright et al, 1999) after long-term culture.…”
Section: Discussionmentioning
confidence: 99%